The cost of HIV testing at five district health facilities intervented poct model to confirmation HIV detected - Nguyen Viet, Nga; Ho Thi, Hien; Nguyen Thanh, Long (Tạp chí Khoa học Nghiên cứu Sức khỏe và Phát triển, 2021)
Objective: HIV testing is the only method to confirm people infected with HIV. There are many models providing HIV testing services. HIV testing cost is an important component for the investment and strategic direction of policies and programs on HIV. This paper describes HIV testing costs of HIV confirmatory testing by using three rapid diagnostic tests at district level (POCT- Point of Care testing). Methods: cross-sectional study design was employed, costs are calculated using the cost-allocation method based on the proportion of resources used for the personnel, investment such as infrastructure and equipments, routine operational costs including test kits and consumable supplies, administration and training, fuel costs using for HIV testing in the laboratory, transporting the sample to province for HIV positived confirmation and HIV confirmatory test at the province. Five district health centers (DHC) thực hiện mô hình can thiệp POCT HIV were studied, HIV tests were conducted for 4,636 clients in 2016. Results : 201 HIV positive cases were detected; after implementing the POCT model to confirm HIV status at these five DHCs, the cost per HIV screening test case is 7,4 USD on average; and cost per an HIV comfirmatory test is 206,8 USD. Conclusion: Applying the POCT model of HIV helps reducethe cost of HIV testing because of saving cost for sample transportion and implementing confirm HIV detected more in provincal standard laboratory. It should be expanded to use especially limitted resource settings in Vietnam